Peran Guru sebagai Fasilitator dalam Meningkatkan Kreativitas Anak Sekolah Dasar - Isari, Alya; ZD, Nadhifa Nur Rahmah; Candra S, Mia Apta; Hidayat, Akhmad Faisal (Lembaga Yasin AlSys, 2025)
This study aims to explore the role of teachers as facilitators in enhancing student creativity at the elementary school level. In the context of 21st-century learning, teachers are no longer merely transmitters of information, but rather guides and companions in the process of developing students’ potential. The method used is a literature review, analyzing various relevant sources on teacher strategies for facilitating creativity. The findings indicate that teachers who act as facilitators must be able to recognize the diverse characteristics of students, apply innovative teaching methods, and utilize appropriate media to encourage active participation and critical thinking. Constructive feedback, a supportive classroom environment, and freedom of expression are key factors in fostering creative skills and problem-solving abilities. The study concludes that the teacher’s role as a facilitator is crucial in preparing students to become independent, innovative, and adaptable individuals in facing future challenges. The implications highlight the need for teachers to continuously develop their pedagogical competence and creativity in teaching practices to create transformative learning experiences.